2001
DOI: 10.1080/00224540109600547
|View full text |Cite
|
Sign up to set email alerts
|

Extraterrestrial Beliefs and Experiences: An Application of the Theory of Reasoned Action

Abstract: The authors expanded the applicability of I. Ajzen and M. Fishbein's (1980) theory of reasoned action by assessing the participants' beliefs, attitudes, and experiences related to sightings of unidentified flying objects (UFOs) and to alien abductions. The authors designed and administered a survey on UFO phenomena to 398 Canadian students. The survey contains items relating to each component of Ajzen and Fishbein's model, as well as scales that evaluate paranormal beliefs and social desirability. A majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Finally, our results showed that there was no sex difference in beliefs about extraterrestrial beliefs. Although this stands in contrast to previous work suggesting that men are more likely than women to believe that UFOs are evidence of intelligent extraterrestrial life and to believe in alien visitations (Goode, 2000; Irwin, 1993; Patry & Pelletier, 2001; Rice, 2003), it is consistent with the lack of significant sex differences found in previous work using the same measure of extraterrestrial beliefs (Swami et al, 2009, in press). In contrast to previous studies (Goode, 2002; Swami et al, 2009, in press), however, our results suggest that higher education was associated with lower paranormal extraterrestrial beliefs.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Finally, our results showed that there was no sex difference in beliefs about extraterrestrial beliefs. Although this stands in contrast to previous work suggesting that men are more likely than women to believe that UFOs are evidence of intelligent extraterrestrial life and to believe in alien visitations (Goode, 2000; Irwin, 1993; Patry & Pelletier, 2001; Rice, 2003), it is consistent with the lack of significant sex differences found in previous work using the same measure of extraterrestrial beliefs (Swami et al, 2009, in press). In contrast to previous studies (Goode, 2002; Swami et al, 2009, in press), however, our results suggest that higher education was associated with lower paranormal extraterrestrial beliefs.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, although most scientists are sceptical of claims that unidentified flying objects (UFOs) are of extraterrestrial origin, some sections of the general public consider UFOs to be evidence of intelligent extraterrestrial life (e.g. Biasco & Nunn, 2000; Gallup, 1997; Irwin, 2009; Patry & Pelletier, 2001).…”
Section: Paranormal and Superstitious Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to TRA, values held and opinions espoused by individuals' important referents tend to influence the behaviors of those individuals. TRA has proven useful as a means of explaining diverse decision-making situations (Patry and Pelletier 2001), such as those that will be examined in this study. A significant relationship was also observed to exist between subjective norms and behavioral intentions.…”
Section: Hypothesized Relationshipsmentioning
confidence: 99%